New Pole In New Poland. Upbringing according to Jan Stachniuk - Gulanowski, Jacek (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
Jan Stachniuk was a Polish thinker, who created the ideology of culturalism or the so-called “ideal of Zadruga”. According to his concepts, the aim of mankind is the maximal control of the world, which is the expression of is culture. The opposition of this tendency is the nihilistic striving for vegetation, the expression of which is the so-called “anti-culture”. This dualistic vision of mankind and the universe is expressed in Stachniuk’s vision of education. On the one hand, Stachniuk negatively evaluates the existing Polish education, the roots of which he found in Counter-Reformation, which he considered an expression of anti-culture. On the other hand, he believed that only through a transformation of the ideal of education can a cultural change be achieved. He called for a cultural revolution and the realisation of the ideal of “Zadruga-based state”, which will take total control of education and create a new man.
Keywords: Jan Stachniuk; Zadruga